Multi-element coating titanium anode and preparation method and application thereof

By using multi-coated titanium anode in the zinc electrostatic accumulation industry and using metal oxide coatings of IrO2, RuO2, SnO2 and MnO2, the problems of low strength and lead pollution of lead-based alloy anode are solved, and the efficient and low-energy consumption zinc electrostatic accumulation process is achieved, and the service life of the titanium anode is extended.

CN119877043APending Publication Date: 2025-04-25YUNNAN NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510093750.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The lead-based alloy anode used in the existing zinc-electricity industry has problems of low strength, high energy consumption and lead pollution, and the application of titanium electrodes in acidic oxygen evolution environments is limited by high cost and short life.

Method used

A multi-coated titanium anode, including a titanium matrix and a metal oxide coating composed of IrO2, RuO2, SnO2 and MnO2, was prepared by the sol-gel method, and the molar ratio of Ir, Ru, Sn and Mn was regulated to improve catalytic activity and stability.

Benefits of technology

It realizes the reduction of the anode oxygen evolution potential, improves the reaction rate, extends the service life of the titanium anode, reduces the preparation cost, and improves the current efficiency of the zinc electrodeposition process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119877043A_ABST
    Figure CN119877043A_ABST
Patent Text Reader

Abstract

The invention discloses a multi-element coating titanium anode and a preparation method and application thereof, and belongs to the technical field of titanium electrodes, and the multi-element coating titanium anode comprises a titanium substrate and a metal oxide coating; the metal oxide coating layer comprises IrO2, RuO2, SnO2 and MnO2, and the metal oxide coating layer is a metal oxide coating layer; the molar ratio of Ir to Ru to Sn to Mn in the metal oxide coating is (20-30): (64-76): (1-5): (2-10). The invention further discloses a method for preparing the multi-element coating titanium anode through a sol-gel method and application of the multi-element coating titanium anode in zinc electrodeposition. Compared with a titanium anode surface prepared by a thermal decomposition method, the titanium anode surface prepared by the sol-gel method is finer and more uniform in crystal grain, fine and uniform in surface crack, larger in specific surface area and better in electro-catalytic activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of titanium electrodes for oxygen evolution in acidic systems such as zinc electrowinning, and in particular relates to a multi-element coating titanium anode and a preparation method and application thereof. Background Art

[0002] At present, the anodes used in the zinc electrowinning industry are basically lead-based alloy anodes. Lead-based alloy anodes have problems such as low strength, high cell voltage, and high energy consumption. In addition, lead will inevitably dissolve during the electrowinning process, and some of it will be adsorbed or deposited on the cathode zinc sheet, increasing the lead content in the cathode zinc sheet and affecting the quality of zinc. In addition, lead is a toxic heavy metal, and excessive accumulation in the body will cause great harm to the human body.

[0003] Titanium electrodes have the advantages of light specific gravity, good conductivity, strong corrosion resistance, high mechanical strength, and long working life. Their excellent resistance to wet chlorine is unmatched by other metal materials. The reason why they have not been used in the electrolytic zinc oxygen evolution environment is mainly because the cost of rare metal coating raw materials is high, the bonding strength is low, the life is short, and the acidic oxygen evolution conditions have strict requirements on the performance of the coating anode. The composition and structure of the coating material are one of the most important factors determining the performance of the electrode. Therefore, as soon as the titanium anode came out, a lot of research work was carried out around the coating. This is an important stage in the development of the titanium anode field. Its main purpose is to seek synergistic effects through multi-component coating materials, so that the components can achieve close electronic connections and improve the electrode catalytic activity. In the prior art, the preparation methods of general metal oxide coated electrodes mainly include electrodeposition and brushing-thermal decomposition, but the electrodes obtained by most methods have poor corrosion resistance and short service life. The preparation process is complicated and mainly based on precious metals, and the cost is relatively high.

[0004] Therefore, how to provide a new type of titanium anode material to replace the traditional lead-based alloy anode to avoid lead pollution and improve the quality of zinc is a technical problem that technicians in this field urgently need to solve. Summary of the invention

[0005] In order to solve the above technical problems, the present invention proposes a multi-element coating titanium anode and a preparation method and application thereof.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A multi-element coating titanium anode, comprising a titanium substrate and a metal oxide coating;

[0008] The metal oxide coating includes IrO2, RuO2, SnO2 and MnO2;

[0009] Wherein, the molar ratio of Ir, Ru, Sn and Mn in the metal oxide coating is (20-30):(64-76):(1-5):(2-10).

[0010] Beneficial effects: IrO2 in the present invention can maintain high stability in an oxygen evolution environment, and has a low oxygen evolution overpotential; RuO2 has excellent electrochemical properties, chemical stability and high catalytic activity; SnO2 has certain catalytic activity, and can improve the conductivity of the coating, refine the coating crystal structure, and is cheaper than Ir and Ru; MnO2 has two different types of oxides, which can reduce the activation energy of the reaction, thereby accelerating the reaction speed, improving the reaction efficiency, and can resist acid corrosion in an acidic environment, thereby increasing the service life of the anode. At the same time, the price is relatively cheap, and the use of precious metals can be reduced, thereby reducing costs. The present invention fully mixes substances containing elements such as ruthenium, iridium, tin, and manganese, obtains corresponding oxides after heat treatment, and uses oxide structural defects and multivalent states to achieve redox catalytic effects. At the same time, the crystal structures of the four oxides are not much different, and a solid solution containing four effective material components can be formed during the heat treatment process, which can further improve the stability of the anode coating. The coating prepared under the above ratio of Ir, Ru, Sn and Mn has good catalytic activity and stability, can form a good solid solution structure, and the anode shows excellent performance. In addition, the use of tin and manganese regulates the crystal structure of the coating and reduces the preparation cost.

[0011] A method for preparing a multi-element coating titanium anode comprises the following steps:

[0012] (1) adding a mixed solution of citric acid and ethylene glycol to a mixed solution of ruthenium trichloride and chloroiridic acid, then dropwise adding water and hydrochloric acid and performing ultrasonic treatment to obtain a mixed colloidal solution;

[0013] (2) Adding a colloidal solution of tin tetrachloride and a colloidal solution of manganese nitrate to the mixed colloidal solution, and performing ultrasonic mixing, and obtaining a sol-gel coating solution after standing, coating the sol-gel coating solution on a titanium substrate, drying, and sintering to obtain the multi-element coating titanium anode.

[0014] Beneficial effects: The present invention adds citric acid as a complexing agent in the process of preparing the sol-gel, which can control the concentration of metal ions and play a dispersing role. Ethylene glycol provides -OH groups in the citric acid sol system, plays a dispersing and solvent role, and can also be used as a stabilizer to ensure the stability of the sol. By adjusting the ratio of the two, a sol-gel with high dispersibility and high stability can be prepared, ensuring the uniform mixing of elements such as tin and manganese, and finally obtaining a titanium anode coating with uniform composition.

[0015] Preferably, the mixed solution of ruthenium trichloride and chloroiridic acid in step (1) is obtained by dissolving ruthenium trichloride and chloroiridic acid in anhydrous ethanol and subjecting the mixture to ultrasonic treatment for 10 minutes; and / or,

[0016] The mixed solution of citric acid and ethylene glycol is obtained by dissolving citric acid and ethylene glycol in anhydrous ethanol and then ultrasonically treating for 10 minutes;

[0017] In the mixed solution of citric acid and ethylene glycol, the ratio of the added amounts of citric acid, ethylene glycol and anhydrous ethanol is 1 g:5 mL:5 mL.

[0018] Preferably, the colloidal solution of tin tetrachloride is obtained by adding a mixed solution of citric acid and ethylene glycol and hydrochloric acid to a tin tetrachloride solution and subjecting the mixture to ultrasonic treatment;

[0019] Preferably, the colloidal solution of manganese nitrate is obtained by adding a mixed solution of citric acid and ethylene glycol and hydrochloric acid to a manganese nitrate solution and subjecting the mixture to ultrasonic treatment;

[0020] More preferably, the ultrasonic treatment time is 10 min.

[0021] Beneficial effects: Ultrasonic treatment can make ruthenium trichloride and chloroiridic acid uniformly mixed in ethylene glycol and anhydrous ethanol, and the hydrolysis and polycondensation reaction of the sol can be accelerated by adding a proper amount of hydrochloric acid to form a uniform and stable sol.

[0022] Preferably, the sintering temperature in step (2) is 400-500° C. and the sintering time is 10 min.

[0023] Beneficial effects: At this temperature, the crystals of oxides such as iridium, ruthenium, tin, and manganese are intact, and low temperatures can save energy.

[0024] Preferably, the coating amount in step (2) is 1.0-3.0 mg·cm -2 .

[0025] Beneficial effects: The amount of anode coating is an important guarantee for ensuring anode performance. Too little coating cannot achieve the best catalytic performance, too much coating will result in high costs, and the surface coating is prone to fall off and loss.

[0026] Preferably, the ultrasonic treatment time in step (1) is 1 h; and / or,

[0027] The ultrasonic mixing time in step (2) is 1 hour.

[0028] Beneficial effects: The above ultrasonic mixing conditions can ensure that all substances in the solution are fully mixed.

[0029] Application of a multi-component coated titanium anode in zinc electrowinning.

[0030] Beneficial effect: The zinc electrowinning process is in a sulfuric acid system where the electrolyte is zinc sulfate solution. 2+ Concentration is 40-60g·L -1 , H + Concentration 140-200g·L -1 The anode is a titanium anode and the cathode is an aluminum plate. Oxygen evolution occurs at the anode and Zn2+ The titanium anode surface coating plays a role in catalyzing oxygen evolution. The prepared coated titanium anode has the performance of reducing the anode oxygen evolution potential and increasing the reaction rate. This improves the current efficiency in the zinc electrowinning process and reduces energy consumption.

[0031] Compared with the prior art, the present invention has the following advantages and technical effects:

[0032] The present invention selects Ir and Ru as coating matrix elements, Sn and Mn as main added elements, and obtains a multi-element coated titanium anode. The addition of Sn in the present invention can reduce the grain size of the oxide coating, improve the catalytic activity of the anode, and promote the occurrence of oxygen evolution reaction. The Mn element can form a β-MnO2 solid solution, which greatly enhances the electrocatalytic performance of the titanium anode. Compared with the thermal decomposition method, the surface of the titanium anode prepared by the sol-gel method in the present invention has finer and more uniform grains, finer and more uniform surface cracks, a larger specific surface area, better electrocatalytic activity, and is more suitable for preparing titanium anode coatings. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0034] Figure 1 The XRD patterns of the titanium anodes obtained in Example 1 and Comparative Examples 2-4 are shown;

[0035] Figure 2 The EDS images of the titanium anodes obtained in Example 1 and Comparative Examples 2-4 are shown;

[0036] Figure 3 The cyclic voltammetry test diagrams of the titanium anodes obtained in Example 1 and Comparative Examples 2-4 are shown in Figure 1, where (a) is Ti / IrO2-MnO2; (b) is Ti / RuO2-MnO2; (c) is Ti / SnO2-MnO2; (d) is Ti / IrO2-RuO2-SnO2-MnO2; (e) is the 20 mV·s curve of the titanium anodes obtained in Example 1 and Comparative Examples 2-4. -1 Cyclic voltammetry test result diagram;

[0037] Figure 4 The polarization curve test results of the titanium anode obtained in Example 1 and Comparative Examples 2-4 are shown;

[0038] Figure 5 The corrosion resistance test results of the titanium anodes obtained in Example 1 and Comparative Examples 2-4 are shown;

[0039] Figure 6 The EIS fitting equivalent circuit diagram of the titanium anode obtained in Example 1 and Comparative Examples 2-4;

[0040] Figure 7 Anode strengthening accelerated life test of the titanium anodes obtained in Example 1 and Comparative Examples 2-4;

[0041] Figure 8 The graph is a relationship between the zinc electroplating voltage and time of the titanium anode obtained in Example 1 and Comparative Examples 2-4. DETAILED DESCRIPTION

[0042] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0044] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources;

[0045] The titanium substrate is: a TA2 titanium plate with a size of 30 mm × 10 mm × 3 mm. The titanium plate is polished with sandpaper to remove the surface oxide layer, and the polished titanium plate is placed in a 5% Na2CO3 solution for 60 ℃ alkaline washing for 1 hour, and then the alkaline washed titanium plate is rinsed with deionized water and placed in a 10% oxalic acid solution for etching at a slightly boiling state for 2.5 hours, and finally ultrasonically treated for 10 minutes, fished out and rinsed with deionized water, dried and immersed in anhydrous ethanol for use;

[0046] The hydrochloric acid used had a concentration of 36-38% and was purchased from Chengdu Kelong Chemical Reagent Factory;

[0047] Ruthenium trichloride (containing 40% Ru) was purchased from Kunming Boxi Metal Materials Co., Ltd.;

[0048] Chloroiridic acid (containing 35% Ir) was purchased from Kunming Boxi Metal Materials Co., Ltd.

[0049] Tin tetrachloride (analytical grade) was purchased from Xilong Chemical Co., Ltd.;

[0050] Manganese nitrate tetrahydrate (analytical grade) was purchased from Guangdong Xiaoda Chemical Co., Ltd.;

[0051] Oxalic acid (analytical grade) was purchased from Xilong Chemical Co., Ltd.

[0052] Unless otherwise specified, the room temperature or normal temperature in the embodiments of the present invention refers to 25°C.

[0053] In the following embodiments, due to the certain loss of the coating liquid during the coating preparation process, the molar ratio of the Ir / Ru / Sn / Mn raw materials in the coating preparation process is not exactly the same as the molar ratio of Ir / Ru / Sn / Mn in the coating. This is a normal phenomenon, and those skilled in the art can adjust the amount of raw materials added to the coating liquid according to conventional technical means to obtain a coating with a specified Ir / Ru / Sn / Mn molar ratio.

[0054] Example 1

[0055] A method for preparing a multi-element coating titanium anode comprises the following steps:

[0056] (1) According to the designed Ru / Ir molar ratio of the coating of 75.5:21.5, 0.01546 g of ruthenium trichloride and 0.00987 g of chloroiridic acid were dissolved in 5 mL of anhydrous ethanol and ultrasonically treated for 10 minutes to obtain solution No. 1;

[0057] (2) Dissolve 1 g of citric acid and 5 mL of ethylene glycol in 5 mL of anhydrous ethanol and perform ultrasonic treatment for 10 minutes to obtain solution No. 2;

[0058] (3) Liquid No. 2 was slowly dripped into Liquid No. 1, and 5 mL of deionized water and 1 mL of hydrochloric acid were added dropwise. The mixture was ultrasonicated for 1 hour to obtain a brown colloidal solution, thereby obtaining Liquid No. 3;

[0059] (4) According to the designed coating Ir / Ru / Sn molar ratio of 21.5:75.5:1, tin tetrachloride was weighed and dissolved in 5 mL of anhydrous ethanol, and ultrasonicated for 10 minutes. Then, a mixed solution of 1 g of citric acid and 5 mL of ethylene glycol and 1 mL of hydrochloric acid were added, and ultrasonicated for 1 hour to obtain solution No. 4;

[0060] According to the designed coating Ir / Ru / Sn / Mn molar ratio of 21.5:75.5:1:2, manganese nitrate was weighed and dissolved in 5 mL of anhydrous ethanol, ultrasonicated for 10 minutes, and then 1 g of citric acid, 5 mL of ethylene glycol and 1 mL of hydrochloric acid were added, ultrasonicated for 1 hour to obtain solution No. 5;

[0061] (5) Slowly adding liquid No. 4 and liquid No. 5 into liquid No. 3 under ultrasonic conditions for 1 hour, and standing for more than 38 hours to obtain a sol-gel coating solution;

[0062] (6) The sol-gel coating liquid was evenly applied to the treated titanium electrode with a brush, with a coating amount of 2 mg cm -2 , then place it under an infrared lamp for drying, and then sinter it at 450℃ for 10 minutes. Repeat the above steps until all the coating liquid is applied.

[0063] Example 2

[0064] A method for preparing a multi-element coating titanium anode comprises the following steps:

[0065] (1) According to the designed Ru / Ir molar ratio of the coating of 64.4:27.6, 0.01291 g of ruthenium trichloride and 0.01241 g of chloroiridic acid were dissolved in 5 mL of anhydrous ethanol and ultrasonically treated for 10 minutes to obtain solution No. 1;

[0066] (2) Dissolve 1 g of citric acid and 5 mL of ethylene glycol in 5 mL of anhydrous ethanol and perform ultrasonic treatment for 10 minutes to obtain solution No. 2;

[0067] (3) Liquid No. 2 was slowly dripped into Liquid No. 1, and 5 mL of deionized water and 1 mL of hydrochloric acid were added dropwise. The mixture was ultrasonicated for 1 hour to obtain a brown colloidal solution, thereby obtaining Liquid No. 3;

[0068] (4) According to the designed coating Ru / Ir / Sn molar ratio of 64.4:27.6:1, tin tetrachloride was weighed and dissolved in 5 mL of anhydrous ethanol, and ultrasonicated for 10 minutes. Then, a mixed solution of 1 g of citric acid and 5 mL of ethylene glycol and 1 mL of hydrochloric acid were added and mixed, and ultrasonicated for 1 hour to obtain solution No. 4;

[0069] According to the designed coating Ru / Ir / Mn molar ratio of 64.4:27.6:7, manganese nitrate was weighed and dissolved in 5 mL of anhydrous ethanol, ultrasonically treated for 10 minutes, and then a mixed solution of 1 g of citric acid and 5 mL of ethylene glycol and 1 mL of hydrochloric acid were added, and ultrasonicated for 1 hour to obtain solution No. 5;

[0070] (5) Then, liquid No. 4 and liquid No. 5 are slowly added to liquid No. 3 under ultrasonic conditions for 1 hour, and the mixture is allowed to stand for more than 38 hours to obtain a sol-gel coating solution;

[0071] (6) The sol-gel coating liquid was evenly applied to the treated titanium electrode with a brush, and the coating amount was 2 mg / cm 2 , then place it under an infrared lamp for drying, and then sinter it at 400℃ for 10 minutes. Repeat the above steps until all the coating liquid is applied.

[0072] Example 3

[0073] A method for preparing a multi-element coating titanium anode comprises the following steps:

[0074] (1) According to the designed Ru / Ir molar ratio of the coating of 64.4:27.6, 0.01937 g of ruthenium trichloride and 0.01861 g of chloroiridic acid were dissolved in 5 mL of anhydrous ethanol and ultrasonically treated for 10 minutes to obtain solution No. 1;

[0075] (2) Dissolve 1 g of citric acid and 5 mL of ethylene glycol in 5 mL of anhydrous ethanol and perform ultrasonic treatment for 10 minutes to obtain solution No. 2;

[0076] (3) Liquid No. 2 was slowly dripped into Liquid No. 1, and 5 mL of deionized water and 1 mL of hydrochloric acid were added dropwise. The mixture was ultrasonicated for 1 hour to obtain a brown colloidal solution, thereby obtaining Liquid No. 3;

[0077] (4) According to the designed coating Ru / Ir / Sn molar ratio of 64.4:27.6:1, tin tetrachloride was weighed and dissolved in 5 mL of anhydrous ethanol, and ultrasonicated for 10 minutes. Then, 1 g of citric acid and 5 mL of ethylene glycol mixed solution and 1 mL of hydrochloric acid were added, and ultrasonicated for 1 hour to obtain solution No. 4;

[0078] According to the designed coating Ru / Ir / Mn molar ratio of 64.4:27.6:7, manganese nitrate was weighed and dissolved in 5 mL of anhydrous ethanol, ultrasonically treated for 10 minutes, and then 1 g of citric acid and 5 mL of ethylene glycol mixed solution and 1 mL of hydrochloric acid were added, and ultrasonicated for 1 hour to obtain solution No. 5;

[0079] (5) Then, liquid No. 4 is slowly added to liquid No. 3 under ultrasonic conditions for 1 hour, and the mixture is allowed to stand for more than 38 hours to obtain a sol-gel coating solution;

[0080] (6) The sol-gel coating liquid was evenly applied to the treated titanium electrode with a brush, with a coating amount of 3 mg cm -2 , then place it under an infrared lamp for drying, and then sinter it at 450℃ for 10 minutes. Repeat the above steps until all the coating liquid is applied.

[0081] Example 4

[0082] A method for preparing a multi-element coating titanium anode comprises the following steps:

[0083] (1) According to the designed Ru / Ir molar ratio of the coating of 67.2:28.8, 0.01317 g of ruthenium trichloride and 0.01266 g of chloroiridic acid were dissolved in 5 mL of anhydrous ethanol and ultrasonically treated for 10 minutes to obtain solution No. 1;

[0084] (2) Dissolve 1 g of citric acid and 5 mL of ethylene glycol in 5 mL of anhydrous ethanol and perform ultrasonic treatment for 10 minutes to obtain solution No. 2;

[0085] (3) Liquid No. 2 was slowly dripped into Liquid No. 1, and 5 mL of deionized water and 1 mL of hydrochloric acid were added dropwise. The mixture was ultrasonicated for 1 hour to obtain a brown colloidal solution, thereby obtaining Liquid No. 3;

[0086] (4) According to the designed coating Ru / Ir / Sn molar ratio of 67.2:28.8:2, tin tetrachloride was weighed and dissolved in 5 mL of anhydrous ethanol, and ultrasonicated for 10 minutes. Then, 1 g of citric acid and 5 mL of ethylene glycol mixed solution and 1 mL of hydrochloric acid were added, and ultrasonicated for 1 hour to obtain solution No. 4;

[0087] According to the designed coating Ru / Ir / Mn molar ratio of 67.2:28.8:2, manganese nitrate was weighed and dissolved in 5 mL of anhydrous ethanol, ultrasonicated for 10 minutes, and then 1 g of citric acid and 5 mL of ethylene glycol mixed solution and 1 mL of hydrochloric acid were added, ultrasonicated for 1 hour to obtain solution No. 5;

[0088] (5) Then, liquid No. 4 is slowly added to liquid No. 3 under ultrasonic conditions for 1 hour, and the mixture is allowed to stand for more than 38 hours to obtain a sol-gel coating solution;

[0089] (6) The sol-gel coating liquid was evenly applied to the treated titanium electrode with a brush, and the coating amount was 2 mg / cm 2 , then place it under an infrared lamp for drying, and then sinter it at 450℃ for 10 minutes. Repeat the above steps until all the coating liquid is applied.

[0090] Example 5

[0091] A method for preparing a multi-element coating titanium anode comprises the following steps:

[0092] (1) According to the designed Ru / Ir molar ratio of the coating of 66.5:28.5, 0.01956 g of ruthenium trichloride and 0.01899 g of chloroiridic acid were dissolved in 5 mL of anhydrous ethanol and ultrasonically treated for 10 minutes to obtain solution No. 1;

[0093] (2) Dissolve 1 g of citric acid and 5 mL of ethylene glycol in 5 mL of anhydrous ethanol and perform ultrasonic treatment for 10 minutes to obtain solution No. 2;

[0094] (3) Liquid No. 2 was slowly dripped into Liquid No. 1, and 5 mL of deionized water and 1 mL of hydrochloric acid were added dropwise. The mixture was ultrasonicated for 1 hour to obtain a brown colloidal solution, thereby obtaining Liquid No. 3;

[0095] (4) According to the designed coating Ru / Ir / Sn molar ratio of 66.5:28.5:2, tin tetrachloride was weighed and dissolved in 5 mL of anhydrous ethanol, and ultrasonicated for 10 minutes. Then, 1 g of citric acid and 5 mL of ethylene glycol mixed solution and 1 mL of hydrochloric acid were added, and ultrasonicated for 1 hour to obtain solution No. 4;

[0096] According to the designed coating Ru / Ir / Mn molar ratio of 66.5:28.5:3, manganese nitrate was weighed and dissolved in 5 mL of anhydrous ethanol, ultrasonically treated for 10 minutes, and then 1 g of citric acid and 5 mL of ethylene glycol mixed solution and 1 mL of hydrochloric acid were added, and ultrasonicated for 1 hour to obtain solution No. 5;

[0097] (5) Then, liquid No. 4 is slowly added to liquid No. 3 under ultrasonic conditions for 1 hour, and the mixture is allowed to stand for more than 38 hours to obtain a sol-gel coating solution;

[0098] (6) The sol-gel coating liquid was evenly applied to the treated titanium electrode with a brush, with a coating amount of 3 mg cm -2 , then place it under an infrared lamp for drying, and then sinter it at 450℃ for 10 minutes. Repeat the above steps until all the coating liquid is applied.

[0099] Comparative Example 1

[0100] A method for preparing a multi-element coated titanium anode, which is different from Example 1 in that it is prepared by a thermal decomposition method, specifically comprising the following steps:

[0101] IrCl3, RuCl3, SnCl4 and Mn(NO3)4 were added to a mixed solvent (n-butanol and anhydrous ethanol were mixed in a volume ratio of 1:1) at a molar ratio of Ru / Ir / Ti / Mn of 70:20:3:7, and a coating solution was prepared by ultrasonic mixing treatment. The coating solution was evenly applied to the surface of the titanium substrate with a fine-bristled brush, and infrared irradiation was performed for 30 minutes until the coating solution was completely dry. The coating solution was then transferred to a muffle furnace and calcined at 450°C for 10 minutes. After natural cooling, the coating solution was applied again, infrared irradiation was performed, and calcination treatment was performed. The above steps were repeated many times, and the last calcination treatment time was 1 hour. After natural cooling, the electrode preparation was completed.

[0102] Comparative Example 2

[0103] A method for preparing a binary coated titanium anode, wherein the titanium anode is Ti / IrO2-MnO2, specifically comprising the following steps:

[0104] (1) Dissolve 0.0038 g of chloroiridic acid in 5 mL of anhydrous ethanol and treat with ultrasound for 10 minutes to obtain solution No. 1;

[0105] (2) Dissolve 1 g of citric acid and 5 mL of ethylene glycol in 5 mL of anhydrous ethanol and perform ultrasonic treatment for 10 minutes to obtain solution No. 2;

[0106] (3) Liquid No. 2 was slowly dripped into Liquid No. 1, and 5 mL of deionized water and 1 mL of hydrochloric acid were added dropwise. The mixture was ultrasonicated for 1 hour to obtain a brown colloidal solution, thereby obtaining Liquid No. 3;

[0107] (4) According to the designed coating Ir / Mn molar ratio of 20:7, manganese nitrate was weighed and dissolved in 5 mL of anhydrous ethanol, and ultrasonically treated for 10 minutes, and then 1 g of citric acid and 5 mL of ethylene glycol mixed solution and 1 mL of hydrochloric acid were added, and ultrasonicated for 1 hour to obtain liquid No. 4, and then liquid No. 4 was slowly added to liquid No. 3 under ultrasonic conditions and ultrasonicated for 1 hour, and then allowed to stand for more than 38 hours to obtain a sol-gel coating solution;

[0108] (5) The sol-gel coating liquid was evenly applied to the treated titanium electrode with a brush, and the coating amount was 2 mg / cm 2, then place it under an infrared lamp for drying, and then sinter it at 400℃ for 10 minutes. Repeat the above steps until all the coating liquid is applied.

[0109] Comparative Example 3

[0110] A method for preparing a binary coated titanium anode, wherein the titanium anode is Ti / RuO2-MnO2, specifically comprising the following steps:

[0111] (1) Dissolve 0.0127 g of ruthenium trichloride in 5 mL of anhydrous ethanol and treat with ultrasound for 10 minutes to obtain solution No. 1;

[0112] (2) Dissolve 1 g of citric acid and 5 mL of ethylene glycol in 5 mL of anhydrous ethanol and perform ultrasonic treatment for 10 minutes to obtain solution No. 2;

[0113] (3) Liquid No. 2 was slowly dripped into Liquid No. 1, and 5 mL of deionized water and 1 mL of hydrochloric acid were added dropwise. The mixture was ultrasonicated for 1 hour to obtain a brown colloidal solution, thereby obtaining Liquid No. 3;

[0114] (4) According to the designed coating Ru / Mn molar ratio of 25:7, manganese nitrate was weighed and dissolved in 5 mL of anhydrous ethanol, and ultrasonicated for 10 minutes, and then 1 g of citric acid and 5 mL of ethylene glycol mixed solution and 1 mL of hydrochloric acid were added, and ultrasonicated for 1 hour to obtain liquid No. 4, and then liquid No. 4 was slowly added to liquid No. 3 under ultrasonic conditions and ultrasonicated for 1 hour, and then allowed to stand for more than 38 hours to obtain a sol-gel coating solution;

[0115] (5) The sol-gel coating liquid was evenly applied to the treated titanium electrode with a brush, and the coating amount was 3 mg / cm 2 , then place it under an infrared lamp for drying, and then sinter it at 450℃ for 10 minutes. Repeat the above steps until all the coating liquid is applied.

[0116] Comparative Example 4

[0117] A method for preparing a binary coated titanium anode, wherein the titanium anode is Ti / SnO2-MnO2, specifically comprising the following steps:

[0118] (1) Weigh 0.004 g of tin tetrachloride and dissolve it in 0.0137 mL of anhydrous ethanol, sonicate for 10 minutes, then add 5 mL of deionized water and 1 mL of hydrochloric acid, sonicate for 1 hour to obtain Solution 1;

[0119] (2) According to the designed coating Sn / Mn molar ratio of 3:7, manganese nitrate was weighed and dissolved in 5 mL of anhydrous ethanol, and ultrasonically treated for 10 minutes. Then, 1 g of citric acid and 5 mL of ethylene glycol mixed solution and 1 mL of hydrochloric acid were added, and ultrasonicated for 1 hour to obtain liquid No. 2. Then, liquid No. 2 was slowly added to liquid No. 1 under ultrasonic conditions and ultrasonicated for 1 hour. The solution was allowed to stand for more than 38 hours to obtain a sol-gel coating solution;

[0120] (3) The sol-gel coating liquid was evenly applied to the treated titanium electrode with a brush, with a coating amount of 2 mg cm -2 , then place it under an infrared lamp for drying, and then sinter it at 450℃ for 10 minutes. Repeat the above steps until all the coating liquid is applied.

[0121] Technical effect:

[0122] 1.XRD analysis

[0123] Figure 1 The XRD spectra of several manganese-containing titanium anode coatings show that the main substances of the coatings are rutile phase IrO2 (PDF#86-0330), rutile phase RuO2 (PDF#70-2662), rutile phase SnO2 (PDF#72-1147), β-MnO2 and matrix Ti (PDF#65-3362). The figure contains the relevant characteristic peaks of Ti, which is caused by the X-ray being able to penetrate the coating and reach the surface of the titanium matrix. The relevant characteristic peaks of the titanium matrix mainly appear at 38.187°, 40.010°, 52.801° and 70.403°. The relevant characteristic peaks of rutile-type IrO2, RuO2 and SnO2 mainly appear at 27.841°, 34.964° and 52.801°. Due to the low content of SnO2, the relevant characteristic peaks are not obvious, and its most obvious characteristic peak appears at 38.187°. By comparing the spectrum with the standard spectrum of each phase, it can be found that IrO2, RuO2 and SnO2 have obvious deviations on the (110) and (101) crystal planes. In particular, the peak widths corresponding to the (110) and (101) crystal planes in the coating containing Sn are gradually the widest and the deviation is the most serious, indicating that a solid solution is generated in the coating and it is very likely that a (SnMn)O2 solid solution is generated. This is because Sn 4+ and Mn 4+ The ionic radii of β-MnO2 are very close, 0.069nm and 0.064nm respectively, and they are easy to form solid solutions. β-MnO2 has certain electrocatalytic and redox activities. A certain amount of β-MnO2 in the coating structure can improve the electrocatalytic performance of the coated titanium anode. The Mn content in the coating is 30%. With the addition of different substances, the relevant characteristic peaks of β-MnO2 gradually weaken, indicating that the added elements can affect the crystal structure of β-MnO2. There are no TiO2-related characteristic peaks in all the spectra, indicating that all titanium electrodes and titanium substrates have not been oxidized.

[0124] 2. EDS analysis

[0125] Figure 2The following are EDS images of several manganese-containing titanium anode coatings. It can be clearly seen from the figure that no matter what the surface morphology of the coating is, the main elements Ir, Ru, Sn, and Mn can be evenly distributed in the anode coating, indicating that the anode coating prepared by the sol-gel method and manually brushed multiple times and then heat treated can successfully prepare an anode coating with uniform distribution of metal oxides. It can be seen from the observation that the fluorescence of metal Ti in the cracks of the coating is more obvious, and the fluorescence of other metals mainly appears in the block coating. The gaps in the coating also contain other elements with weak fluorescence, indicating that the coating in the cracks is thinner, but there is no fluorescence of the O element in the cracks, indicating that there is no TiO2 in the coating, and the titanium substrate has not been oxidized during the preparation of the anode coating.

[0126] 4. Electrochemical performance test

[0127] 4.1 Cyclic voltammetry curve test

[0128] The microstructure of the metal oxide anode coating is a porous crack structure, and its actual active area is much higher than the geometric area of ​​the anode surface. In the range where no electrochemical reaction occurs, the anode voltammetric charge (Q) is proportional to the electrochemically active area of ​​the oxide on the anode surface. The size of Q reflects the number of electrochemically active points on the surface of the oxide coating. At the same time, the integral of the cyclic voltammetric curve within a certain range can represent the voltammetric charge. Therefore, the electrocatalytic activity of the anode coating can be reflected by the cyclic voltammetric curve.

[0129] Figure 3 The following are cyclic voltammetry test graphs of several manganese-containing titanium anode coatings. The current response observed in the figure is caused by charge transfer caused by redox reactions on the surface of the active oxide. The broad peaks observed at a potential of -0.8 to 0.8 V are related to the redox transitions of Ir(IV) / Ir(V), Ru(II) / Ru(III), Ru(III) / Ru(IV), and Ru(IV) / Ru(V). In the potential range of 0 to 0.80 V, no oxygen evolution reaction and other side reactions occur at the electrode. The corresponding current is the charging current of the electrode double layer. The size of the area enclosed by the corresponding cyclic voltammetry curve can reflect the number of active points on the electrode surface. Each sample was tested at 5 mV·s -1 , 10mV·s -1 , 20mV·s -1 , 40mV·s -1 Cyclic voltammetry was performed on the coated anode in the measurement mode. Figure 3 It can be seen from parts (a), (b), (c), and (d) that as the scan rate increases, the area enclosed by the sample cyclic voltammetry test curve also increases, and the graphs are basically consistent, which shows that the coated titanium anode has good stability under this condition. Part (e) is in the voltage range of -0.8V to 0.8V, with a scan rate of 20mV·s-1 Cyclic voltammetry curve test under the conditions of. Since the area enclosed by the cyclic voltammetry test curve can reflect the number of active sites on the surface of the anode coating, the larger the area enclosed by the cyclic voltammetry test curve, the more active sites on the surface of the anode coating, and the higher the electrode activity. From part (e), it can be seen that under the same conditions, the area enclosed by the cyclic voltammetry test curve of the Ti / IrO2-RuO2-SnO2-MnO2 coated anode is the largest, and it has the best catalytic activity.

[0130] 4.2 Polarization curve test

[0131] The oxygen evolution polarization curve can reflect the catalytic activity of anodes with different coatings. Figure 4 The polarization curve test diagrams of several manganese-titanium anode coatings are shown in Figure 1. As can be seen from the figure, the oxygen evolution potentials of the several coating anodes are not much different, all around 0.75V.

[0132] Table 1 Kinetic parameters of anode coating

[0133] sample a(mV) <![CDATA[b(mV·dec -1 )]]> <![CDATA[J0(A·cm -1 )]]> <![CDATA[Ti / IrO2-MnO2]]> 52.85 78.27 <![CDATA[1.406×10 -5 ]]> <![CDATA[Ti / RuO2-MnO2]]> 67.13 49.83 <![CDATA[4.917×10 -6 ]]> <![CDATA[Ti / SnO2-MnO2]]> 79.35 44.73 <![CDATA[1.921×10 -6 ]]> <![CDATA[Ti / IrO2-RuO2-SnO2-MnO2]]> 88.84 83.31 <![CDATA[7.525×10 -6 ]]>

[0134] According to the results of the Tafel formula η=a+logi anode polarization experiment, a is the intercept of the Tafel curve, which reflects the difficulty of the electrode electron transfer, and b is the slope. The relationship curve between η and logi was linearly fitted using Nova software to obtain the a and b parameters and calculate the exchange current density (J0). As shown in Table 1, the Tafel slope value b of the Ti / IrO2-RuO2-SnO2-MnO2 coated anode is the largest, which indicates that the electrocatalytic activity of the anode is the largest, which is consistent with the results of the anode polarization experiment. In general, the polarization and reversibility of the electrode reaction can be evaluated by the exchange current density. A higher J0 indicates that the electrode is not easy to polarize and the electrode reaction is easy to occur. As shown in Table 1, the J0 value of the Ti / IrO2-RuO2-SnO2-MnO2 coated anode is also the largest, indicating that the Ti / IrO2-RuO2-SnO2-MnO2 coated anode is not easy to polarize and oxygen evolution reaction is easy to occur.

[0135] 4.3 AC impedance test

[0136] Figure 5 This is the AC impedance spectrum of the manganese-coated titanium anode. Figure 6 The equivalent circuit diagram of the EIS is fitted. The equivalent circuit of the oxygen evolution reaction of the coated titanium anode in the acidic solution can be represented by R s (R f Q l )(R ct Q dl ) is fitted, where R s Represents the electrolyte resistance, R frepresents the film resistance of the metal oxide coating, R ct It indicates the charge transfer resistance during the oxygen evolution reaction of the electrode. The smaller the value, the smaller the resistance of electron transfer during the oxygen evolution reaction, and the easier the reaction is. l represents the surface film resistance of the oxide coating, Q dl Represents the double-layer capacitance of the interface between the reaction coating and the solution. The larger the value, the more active sites on the coating surface; (R f Q l ) represents the anode coating’s own impedance, (R ct Q dl ) represents the impedance between the anode coating and the interface. Table 2 shows the EIS parameters of the titanium anode containing manganese coating. It can be seen from the table that the Q dl The value is the largest, indicating that the coating has the most active sites on the anode surface. Adding Sn can significantly reduce the membrane resistance R of the metal oxide coating. f , but for the charge transfer resistance R ct The effect is not significant, which may be due to the fact that the surface of the Sn-containing coating is relatively dense and the specific surface area is relatively small. By comparison, it can be seen that the conductivity of different metal oxides is from large to small as SnO2>RuO2>IrO2.

[0137] Table 2 EIS parameters of manganese-containing coating anodes

[0138]

[0139] 5. Life test of titanium anode and zinc electrowinning experiment

[0140] 5.1 The titanium anodes coated in Example 1 and Comparative Examples 2-5 were subjected to 1 mol·L -1 In sulfuric acid solution, 1A·cm -2 The accelerated life test was carried out under the current density. When the cell voltage rose to 10V, the electrode was considered to have failed. The relationship between the cell voltage and time during the test was as follows: Figure 7As shown. It can be seen from the figure that the entire process of the enhanced accelerated life test of the titanium anode is divided into three stages: "activation"-"stabilization"-"failure". In the "activation" process, the electrolyte and the coating begin to fully contact. As the contact area increases, the cell voltage will decrease slightly. Then the reaction enters the "stabilization" process, in which the cell voltage is relatively stable. When the coating is close to failure, the cell voltage begins to rise rapidly until the coating completely fails. The results show that the enhanced accelerated life test times of several coating anodes are 95h, 92h, 100h, and 114h, respectively. It can be seen that the addition of Sn can significantly improve the corrosion resistance of the coating, which is related to the fact that Sn can refine the coating grains and reduce the cracks on the coating surface. The fewer the cracks in the coating, the smaller the scouring force of the gas generated during the reaction, and the more stable the coating. Since the metal oxides of Ir, Ru, Sn and Mn can form a solid solution, the multi-element coating structure has better performance.

[0141] 5.2 In order to verify the application of coated titanium anode in production, a continuous zinc electroplating experiment of 24h was carried out on several titanium anodes. The experimental conditions were: the anode used a self-made coated anode plate and a lead-silver alloy plate (Pb-Ag (1%)), the cathode used a pure aluminum plate, and the electrolyte was 55g·L -1 Zn2SO4 solution, electrolyte acidity is H2SO4165 g·L -1 , the electrolytic cell temperature is 38℃~40℃, the electrolysis time is 24h, and the electrolyte flow rate is 470mL·h -1 .

[0142] The relationship between cell voltage and time during electrolytic deposition is as follows: Figure 8 As shown, it can be seen that the titanium anode obtained in Example 1 exhibits very good current efficiency.

[0143] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A multi-element coated titanium anode, characterized in that: including a titanium substrate and a metal oxide coating; The metal oxide coating includes IrO2, RuO2, SnO2 and MnO2; Wherein, the molar ratio of Ir, Ru, Sn and Mn in the metal oxide coating is (20-30):(64-76):(1-5):(2-10).

2. The method for preparing a multi-element coating titanium anode according to claim 1, characterized in that: The following steps are involved: (1) adding a mixed solution of citric acid and ethylene glycol to a mixed solution of ruthenium trichloride and chloroiridic acid, then dropwise adding water and hydrochloric acid and performing ultrasonic treatment to obtain a mixed colloidal solution; (2) Adding a colloidal solution of tin tetrachloride and a colloidal solution of manganese nitrate to the mixed colloidal solution, and performing ultrasonic mixing, and obtaining a sol-gel coating solution after standing, coating the sol-gel coating solution on a titanium substrate, drying, and sintering to obtain the multi-element coating titanium anode.

3. The method for preparing a multi-element coating titanium anode according to claim 2, characterized in that: The mixed solution of ruthenium trichloride and chloroiridic acid in step (1) is obtained by dissolving ruthenium trichloride and chloroiridic acid in anhydrous ethanol and subjecting the mixture to ultrasonic treatment for 10 minutes.

4. The method for preparing a multi-element coating titanium anode according to claim 2, characterized in that: The mixed solution of citric acid and ethylene glycol in step (1) is obtained by dissolving citric acid and ethylene glycol in anhydrous ethanol and subjecting them to ultrasonic treatment for 10 minutes; and / or, In the mixed solution of citric acid and ethylene glycol, the ratio of the added amounts of citric acid, ethylene glycol and anhydrous ethanol is 1 g:5 mL:5 mL.

5. The method for preparing a multi-element coating titanium anode according to claim 2, characterized in that: The colloidal solution of tin tetrachloride in step (2) is obtained by adding citric acid, ethylene glycol and hydrochloric acid to a tin tetrachloride solution and subjecting it to ultrasonic treatment.

6. The method for preparing a multi-element coating titanium anode according to claim 2, characterized in that: The colloidal solution of manganese nitrate in step (2) is obtained by adding citric acid, ethylene glycol and hydrochloric acid to a manganese nitrate solution and subjecting it to ultrasonic treatment.

7. The method for preparing a multi-element coating titanium anode according to claim 2, characterized in that: The sintering temperature in step (2) is 400-500° C. and the sintering time is 10 minutes.

8. The method for preparing a multi-element coating titanium anode according to claim 2, characterized in that: The coating amount in step (2) is 1.0-3.0 mg·cm -2 The quantity is extreme.

9. The method for preparing a multi-element coating titanium anode according to claim 2, characterized in that: The ultrasonic treatment time in step (1) is 4 hours; and / or, The ultrasonic mixing time in step (2) is 1 hour.

10. Use of a multi-component coated titanium anode as claimed in claim 1 in zinc electrowinning.